Availability, distribution and quality of agro-industrial byproducts and compound feeds in Ethiopia - Feyisa, Tesfaye; Tolera, Adugna; Nurfeta, Ajebu; Balehegn, Mulubrhan; Adesogan, Adegbola (Frontiers in Animal Science, 2024)
The limited supply of quality feeds is a major constraint to the improvement of livestock production in Ethiopia. The expansion of agro-industries in Ethiopia, over the last three decades, has created an opportunity for an increased supply of agro-industrial by-products as a source of feed for livestock. This study was conducted to assess the availability, distribution, and quality of agro-industrial byproducts and compound feeds in Ethiopia. About 310 flour mill factories, 194 oil factories, 13 brewery factories, 7 sugar factories, 4 malt factories, 2 meat and bone meal processing plants, 8 limestone factories, and 112 feed processing plants were surveyed to assess the availability and distributions of agro-industrial byproducts and compound feeds. A total of 757 feed samples were collected for evaluating nutritional values. The annual production of agro-industrial byproducts ranges from 18,065 tons DM/year (abattoir byproducts) to 3,092,035 tons DM/year (malt byproducts) and the total annual production of the different agro-industrial by-products amounts to 5,245,854 tons DM. The annual production of compound feeds was reported to be 5,812,608 tons DM. All agro-industries are processing under their capacity, ranging from 11.7% in sugar factories to 93% in breweries. Shortage and seasonal fluctuation of supply of raw materials (34.8%), high price and price fluctuations of raw materials (17.5%) and electric power interruptions (17.5%) were the major challenges faced by different agro-industries. The crude protein (CP) concentrations of agro-industrial byproducts ranges from 6.2% in maize grain screening to 15.9% in wheat bran for flour mill byproducts; 28% in cotton seed cake to 49.7% in groundnut cake for oilseed cakes and 14.8% in areqe atela to 24.8% in brewery spent grains for brewery and local distillery byproducts. High protein or energy contents of agro-industrial byproducts indicated their potential to be utilized in intensive livestock rations. Thus, it is necessary to create enabling conditions to allow the existing agro-industries to operate at full capacity and to attract new ones into the business to boost the production and availability of agro-industrial by-products needed as main inputs to manufacture of compound feeds.